2017
DOI: 10.1002/ptr.5783
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety ofCissus quadrangularisL. in Clinical Use: A Systematic Review and Meta-analysis of Randomized Controlled Trials

Abstract: Cissus quadrangularis L. (Cissus) is a medicinal plant commonly used for centuries for various conditions, but lacks critical appraisal of its clinical effects. This study aimed to determine the efficacy and safety of Cissus in all conditions. Publications from 12 electronic databases were searched from inception through November 2016. A total of nine studies with 1108 patients were included. Each outcome was pooled using a random effects model. Effects of Cissus on hemorrhoid symptoms were not different from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…However, these effects were observed in RCTs of only 8 to 10 weeks’ duration, and all of the two to three studies conducted on each of these herbal medicines were by the same research groups, which introduces a high risk of selective reporting and confirmation bias, therefore, more evidence is needed before a definitive decision on their effect on weight loss can be reached. This conclusion is consistent with a 2017 systematic review of C. quadrangularis and a 2013 systematic review of I. gabonensis . In contrast, our review revealed inconsistent results among the few studies on I. paraguariensis and G. glabra , perhaps due to the varied combination preparations studied.…”
Section: Discussionsupporting
confidence: 90%
“…However, these effects were observed in RCTs of only 8 to 10 weeks’ duration, and all of the two to three studies conducted on each of these herbal medicines were by the same research groups, which introduces a high risk of selective reporting and confirmation bias, therefore, more evidence is needed before a definitive decision on their effect on weight loss can be reached. This conclusion is consistent with a 2017 systematic review of C. quadrangularis and a 2013 systematic review of I. gabonensis . In contrast, our review revealed inconsistent results among the few studies on I. paraguariensis and G. glabra , perhaps due to the varied combination preparations studied.…”
Section: Discussionsupporting
confidence: 90%
“…A systematic review on the randomized controlled trials available in the present concluded that no serious adverse effects were reported with the use of Cissus quadrangularis (Sawangjit et al, 2017).…”
Section: Safetymentioning
confidence: 71%
“…It has been utilized in Ayurveda as an alternative medicine to treat bone fracture, digestive, eye, ear diseases, and asthma for more than a century [ 9 , 11 ]. Fresh stems and roots of C. quadrangularis have been used as food and management for various ailments [ 11 , 13 ]. Several studies have shown that C. quadrangularis has compounds such as friedelin, α-amyrone, resveratrol, piceatannol, quercetin, and pallidol with various metabolic and pharmacological properties [ 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%